Theoretical models of educational management - Mukhtarova, A. N. (Journal of Economic Research & Business Administration, 2015)
The present article is devoted to the issues of existing theoretical models in educational management. The classification of models, international experience and Kazakhstani educational management were discussed. Educational Management as a separate industry science is actively developing in many educational systems around the world. This article utilized such scientific methods as a descriptive analysis, synthesis, comparison, generalization. However, the theory of educational management is still not completely understood, in particular in developing and non-English speaking countries. There is a need to review the existing models of educational management, especially the bureaucratic model of educational management; analysis of theoretical models showed that educational management requires further study of practices in different countries; also there is suggested a possible scenario of educational management developement in Kazakhstan.